Aluminum Aryloxide Compounds as Very Active Catalysts for Glycidyl Methacrylate Selective Ring‐Opening Polymerization. Issue 5 (1st February 2018) - Muñoz, M. Teresa; Palenzuela, Miguel; Cuenca, Tomás; Mosquera, Marta E. G.
Abstract: New aluminum compounds of the type [AlXMe(OAr)] n [X=Me (1 ), Cl (2 )] bearing the bulky ligand OAr=2, 6‐bis(diphenylmethyl)‐4‐ tert ‐butylphenoxide were synthesized and characterized in the solid state and in solution. These compounds are mononuclear in solution. Their catalytic activity in glycidyl methacrylate (GMA) polymerization was explored. This monomer contains two different functionalities, oxirane and methacrylate, and, hence, could give functionalized polymers by ring‐opening polymerization (ROP) or vinyl polymerization. Catalysts1 and2 could selectively polymerize the oxirane functionality in minutes at room temperature, leaving the methacrylate group intact. Remarkably, 1 and2 are the most active catalysts in ROP processes of GMA described so far. Abstract : Opening the ring : Mononuclear derivatives of the type [AlMeX(OAr)] bearing very bulky aryloxide ligands are prepared and proven to be the most active catalysts for the selective ring‐opening polymerization of the bifunctional monomer glycidyl methacrylate.